The Influence of Principal’s Academic Supervision and Work Environment on Teacher’s Performance - Nurizatiningsih, Nurizatiningsih; Ahyani, Nur; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the effect of the Principal's Academic Supervision and the work environment on the performance of SMK teachers in Mesuji District. This type of research is quantitative research with a research design using an ex post facto research design. The sample in this study is a total of all SMK teachers in Mesuji District. consisting of 100 teachers. Data collection technique using a questionnaire. Data analysis techniques using quantitative descriptive analysis techniques, and multiple regression. The results of this study state that 1) there is a significant effect of Principal Academic Supervision on the performance of SMK teachers in Mesuji District; 2) there is a significant effect of the work environment on the performance of SMK teachers in Mesuji District; 3) there is a jointly significant effect of the Principal's Academic Supervision and the work environment on the performance of SMK teachers in Mesuji District.